Linguosuggestive technologies of influence in the doctrinal documents of the Russian Federation - Karnaukh, Serhii (Current issues of Ukrainian linguistics: theory and practice, 2024)
The article examines the doctrinal documents of the aggressor country (Military Doctrine of the Russian Federation, Information Security Doctrine of the Russian Federation, National Security Strategy of the Russian Federation) as discursive events that create the Russian conceptual picture of the world – an alternative pseudo-reality based on simulacra-substitutions and demonstrating false information about the global security situation and the total threat to the sovereignty of the Russian Federation. It is proved that the doctrinal documents of the Russian Federation are based on the conceptual apparatus of information warfare, that is enshrined in the dictionary edited by D. Rogozin "War and Peace in Terms and Definitions". Linguosuggestive technologies are considered in this dictionary as a weapon of information warfare, in particular, the language of war is defined as "a way of manipulating public opinion by linguistic means". It is determined that the texts of doctrinal documents of the Russian Federation use linguistic and suggestive technologies of persuasion without critical analysis of information, simulation and intellectual reception. The technology of persuasion without critical analysis of information is used to create a false image of the Russian Federation as a democratic state that implements traditional values, and therefore must resist the information aggression of Western countries that are in a cultural crisis. With the help of simulacra technology, an alternative reality is being built, in which all Russia’s destructive actions are attributed to Western countries and Ukraine. The technology of intellectual reception is used to consolidate generalizations acceptable to the Putin regime, which are then broadcast through all official and media channels and form the position of Russian citizens on the need to protect themselves from the West and Ukraine. These linguistic and suggestive technologies are pragmatically aimed at invading the cognitive space of the addressee – Russian citizens, aggressively imposing a negative attitude towards STRANGERS (Western countries and Ukraine). Military aggression is presented as a defense against Western encroachment on Russia’s sovereignty and territorial integrity; Russia’s invasion of Ukraine is presented as an unresolved regional conflict. As a result, the recipient of the information does not identify the substitution of reality, the pragmatic result of which is the support of Russia’s military aggression in Ukraine.